Corrosion behavior of silicon nitride bonded silicon carbide refractory material by molten copper and copper slag. Issue 5 (1st April 2017) - Yurkov, Andrey; Malakho, Artem; Avdeev, Victor
Abstract: Silicon Carbide refractories may be used in contact with copper and copper slags. The object for the investigation of corrosion by the melt of copper and the copper slag was SiC siphon block of the slag collector in the runner of the cathode shaft furnace. It is exposed to the permanent flow of copper with small amount of slag. Slag on the surface of the melt is stopped by siphon block and it suffers the most extensive corrosion wear, but the same time it is a good object for investigation, because different parts of this plate are exposed to intensive corrosion by different corrosive agents. General observations show, that the corrosion of Si3 N4 -SiC by slag is sufficiently more extensive and the wear is about 3 mm per month, while the wear by the flowing copper is below 1 mm per month. The observation of the cross section of the exposed Si3 N4 -SiC plate on macro level shows 4–5 zones of different color. Microstructural observations show almost no changes of the material in direct contact with molten copper without exposure of air, that suggests slow dissolution of Silicon Carbide and Silicon Nitride in the flowing melt of copper (physical dissolution in case of permanent removal of reactants). The most severe wear of Si3 N4 -SiC refractory is by slag, because the chemical erosion takes place.